Perancangan Sistem Informasi Akuntansi Persediaan Pada Cv Bintang Karya Nusantara Menggunakan Microsoft Excel - Finjela Nanda Sridinar Sridinar; Hariadi Yutanto; Reza Tianto Tianto (Wahana, 2023)
CV Bintang Karya Nusantara is a service and trading company that provides consumer needs in the field of information technology. Based on the results of interviews, it is known that the incoming and outgoing inventory is not directly inputted and the company uses software application excel only as a recording medium without using several functions (formulas). As a result, information on the amount of inventory cannot be known to be up to date errors input so that there is a difference between the physical amount and the recording. To overcome these problems, researchers designed an inventory accounting information system to produce inventory information more quickly and accurately so that CV Bintang Karya Nusantara could operate optimally. The research method used in this research is system design. The result of this system is an Excel for Accounting software that can be used by companies to collect inventory data, customer data, supplier data, incoming goods, outgoing goods, sales returns, purchase returns and can be used to generate more detailed reports on merchandise inventory efficient, fast and accurate.